Simulation and Control of Multipurpose Wheelchair for Disabled/elderly Mobility - Normaniha, Abd Ghani; Tokhi, M. O. (IOS Press, 2016)
This paper presents investigations into the development of modelling and control strategies for a multipurpose wheelchair as mobile transporter for elderly and disabled people. The research is aimed at helping people with physical weakness/disabilities in their upper and lower extremities to move independently without human intervention. A novel reconfiguration which allows multi-task operations in the same wheelchair system with improved design is modelled in Visual Nastran 4D (VN4D) software. A modular fuzzy logic control mechanism with integrated phases is introduced for the overall operations and two-wheeled stabilization of the wheelchair. It is shown that the proposed modular fuzzy control approach is able to ensure system stability while performing multipurpose tasks such as manoeuvrability on flat surfaces, stairs climbing (ascending and descending), standing in the upright position on two wheels and transformation back to standard four wheels with up to 50% less initial torque in comparison to previous designs.